Assessing the Influence of Corporate Social Responsibility on Consumer Satisfaction and Perceived Value - Tariq, Haleema; Rehman, Chaudhary Abdul (Advances in Social Sciences Research Journal, 2017)
The corporate social responsibility and corporate social performance tend to increase the productivity and the customer satisfaction by reducing the overall cost. The respondents who buy and use cars give due importance to the factors such as the labour practices, product quality and services and the findings depict that CSR not only increases the overall performance but also influences the customer satisfaction. The corporate social performance and customer satisfaction is affected by CSR in car industry settings in Pakistan. The main purpose is to identify the impact of corporate social responsibility on consumer satisfaction and perceived value for automobile users. Multi-item scale was adapted to find out that how the perceived value and satisfaction of customers is driven by the factors of CSR. The primary data in form of survey questionnaires were collected from 292 car users and buyers from various areas in Lahore, Pakistan on the basis of simple random sampling. The study reveals a significant and positive relationship between customer satisfaction and perceived values but there is no significant relationship exists among the corporate social responsibility and customer satisfaction. This research study enlightens the areas in which the corporate social responsibility may pay off by doing better. The policy makers and car manufacturers may be benefited through implementing such categories for improving social performance and service quality. Some longitudinal designs and comparative analysis with some other sectors may be used in order to increase the external validity of results.